Clinical Outcomes of Second-Line Chemotherapy after Progression on Nab-Paclitaxel Plus Gemcitabine in Patients with Metastatic Pancreatic Adenocarcinoma - Lee, Kyoungmin; Bang, Kyunghye; Yoo, Changhoon; Hwang, Inhwan; Jeong, Jae Ho; Chang, Heung-Moon; Oh, Dongwook; Song, Tae Jun; Park, Do Hyun; Lee, Sang Soo; Lee, Sung Koo; Kim, Myung-Hwan; et al. (Cancer research and treatment, 2020)
Since the introduction of nab-paclitaxel plus gemcitabine (nab-P+GEM) as first-line (1L) treatment for metastatic pancreatic adenocarcinoma (mPDAC), optimal second-line (2L) chemotherapy after progression is unclear. We assessed clinical outcomes of 2L chemotherapy for disease that progressed on 1L nab-P+GEM. Among the 203 patients previously treated with 1L nab-P+GEM for mPDAC at Asan Medical Center, between February and December 2016, records of 120 patients receiving 2L chemotherapy after progression on nab-P+GEM were retrospectively reviewed. The response rate and survival were evaluated along with analysis of prognostic factors. Fluoropyrimidine-oxaliplatin doublets (FOLFOX or XELOX) were used in 78 patients (65.0%), fluoropyrimidine monotherapy in 37 (30.8%), and liposomal irinotecan plus fluorouracil in two (1.7%). The median progression-free survival (PFS) and overall survival (OS) were 3.29 months and 7.33 months from the start of 2L therapy. Fluoropyrimidine-oxaliplatin regimens and fluoropyrimidine monotherapy did not yield significantly different median PFS (2.89 months vs. 3.81 months, p=0.40) or OS (7.04 months vs. 7.43 months, p=0.86). A high neutrophil-lymphocyte ratio (> 2.2) and a short time to progression with 1L nab-P+GEM (< 6.4 months) were independent prognostic factors of poor OS with 2L therapy. 2L fluoropyrimidine-oxaliplatin doublets and fluoropyrimidine monotherapy after failure of 1L nab-P+GEM had modest efficacy, with no differences in treatment outcomes between them. Further investigation is warranted for the optimal 2L chemo-regimens and sequencing of systemic chemotherapy for patients with mPDAC.